KURIKULUM PENDIDIKAN BAHASA ARAB DALAM DINAMIKA SEJARAH PENDIDIKAN DI INDONESIA - Iis Susiawati; Dadan Mardani; Muhammad Faiz Alhaq; Rahmi Aisyah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2024)
This article aims to discuss in depth the Arabic language education curriculum and its development in the dynamics of the history of education in Indonesia as a historical study of curriculum. Based on the data collection technique, this library research uses the documentation method, by seeking information and data from written documents, which are obtained to support the theme of the discussion in the article, namely with the aim of obtaining data and explanations regarding the theme of the article's discussion which can be concluded and presented in detail . The result is that educational institutions need to deal with conditions that have changed along with the development of science and technology by being ready to deal with them and being anticipatory and productive as practiced by developed countries. Theological principles, philosophical principles, psychological principles, socio-cultural principles, and science and technology principles are five principles that can become the basis for formulating an Arabic language education curriculum in Indonesia while still referring to the general goals and specific objectives of learning Arabic. The conclusion is that the development of the Arabic language education curriculum is a necessity along with the times.